Self-Talk Therapy as A Method for Managing Anxiety and Stress in The Community of RW 12 In the Gebang Village, Patrang District, Jember: Terapi Self Talk Sebagai Metode Mengatasi Kecemasan dan Stres pada Masyarakat RW 12 di kelurahan Gebang Kecamatan Patrang Jember (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
Stress is a common issue experienced by individuals, characterized by feelings of pressure when faced with situations that deviate from their expectations. Prolonged stress can lead to anxiety, anger, and frustration, potentially resulting in sleep disturbances, irritability, headaches, and various other health symptoms. Therefore, it is crucial to address stress to enhance human quality of life, with one approach being the utilization of self-talk techniques. The aim of this community service initiative is to enhance public understanding regarding stress management through self-talk techniques. Mental health education activities were conducted in RW 12, Gebang Village, Patrang District. The educational methods included lectures and demonstrations by students, with a sample size of 30 individuals selected using quota sampling. Results from the mental health education activities concerning stress management in RW 12 indicate high enthusiasm among the community members. This was evidenced by active participation during the Q&A session, where all participants were able to answer questions posed by the presenters. Participants reported that the taught therapy was easy to implement and, when rationalized, could alleviate negative thoughts within the community. Mental health education utilizing lecture and demonstration techniques proved effective in enhancing community knowledge regarding stress management.